2018
DOI: 10.1177/1077558718781606
|View full text |Cite
|
Sign up to set email alerts
|

The Privatization of Public Hospitals: Its Impact on Financial Performance

Abstract: This study examined the effects of public hospitals' privatization on financial performance. We used a sample of nonfederal acute care public hospitals from 1997 to 2013, averaging 434 hospitals per year. Privatization was defined as conversion from public status to either private not-for-profit (NFP) or private for-profit (FP) status. Financial performance was measured by operating margin (OM) and total margin (TM). We used hospital level and year fixed effects linear panel regressions with nonlagged independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…For Hypothesis 1, privatization was a binary variable recoded as "1" if the hospital converted to private status (the year of privatization and following years were recoded as 1) and "0" if the hospital remained public (12,14). For Hypothesis 2, privatization had two dummy variables.…”
Section: Independent Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…For Hypothesis 1, privatization was a binary variable recoded as "1" if the hospital converted to private status (the year of privatization and following years were recoded as 1) and "0" if the hospital remained public (12,14). For Hypothesis 2, privatization had two dummy variables.…”
Section: Independent Variablesmentioning
confidence: 99%
“…The dummy variable "privatization to for-profit status" was recoded as "1" if the hospital converted to private for-profit (the year of privatization and following years were recoded as "1") and "0" if the hospital stayed public. The other dummy variable "privatization to not-for-profit status" was recoded as "1" if the hospital converted to private not-forprofit (the year of privatization and subsequent years were coded as "1") and "0" if the hospital stayed public (12,14,43).…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…9,21,23 For-profit hospitals tend to charge higher prices than public and nonprofit hospitals. 19,23,24 This, in part, may reflect their wider profit margins 25,26 and higher overhead and capital expenditures. [27][28][29][30] Despite higher costs to the payor, for-profit hospitals often outsource and are thus able to minimize the number of employed staff -particularly non-physician staff.…”
Section: Why Is It That For-profit Hospitals Do Not Deliver Superior mentioning
confidence: 99%
“…25,[37][38][39][40][41] Third, while some cross-sectional studies have found that forprofits are less efficient because they tend to acquire inefficient public and nonprofit organizations, 9 other longitudinal studies suggest that for-profit entities streamline the public and nonprofit hospitals they acquire and thereby achieve greater efficiency. 26,33 Research Questions If, as the literature suggests, consistently superior performance on patient outcomes or economic efficiency does not explain the growth of for-profit hospitals, other factors must be explored. financing costs are lower.…”
Section: Why Is It That For-profit Hospitals Do Not Deliver Superior mentioning
confidence: 99%